Modeling Groundwater Flow Dynamics Using the Master Recession Curve: Insights from Small Island Watersheds in Ambon, Indonesia - Bokiraiya Latuamury; John Frangky Sahusilawane; Husain Marasabessy; Wilma Nancy Imlabla; Gunawan Hartono; Much Hidayah Marasabessy (Forest and Nature, 2025)
Understanding groundwater flow dynamics through the Master Recession Curve (MRC) is critical in evaluating groundwater behavior following periods of extraction or cessation of rainfall. This study employs the Depuit-Boussinesq model for aquifer flow storage, wherein recession coefficients and constants are primary determinants of the MRC’s shape. This research aims to visualize the MRC using the Depuit-Boussinesq model to assess flow storage in small watershed areas within Ambon City, Maluku Province, Indonesia. The research methodology involved hydrological analysis across five watersheds, namely Wae Tomu, Wae Ruhu, Wae Batu Merah, and others, to model the relationship between recession constants, recession coefficients, and the MRC’s shape. Data collection included groundwater head and aquifer parameters measurements over the study period. The visualization results reveal variations in MRC shapes among the watersheds. The Wae Tomu Watershed exhibits a steeper MRC, indicating a sharp decline in groundwater head. In contrast, the Wae Ruhu and Wae Batu Merah Watersheds display more gradual MRCs, reflecting slower and steadier head declines. The recession constant of the Wae Ruhu Watershed is higher, indicating a larger storage capacity, while the Wae Tomu Watershed has a lower recession constant, representing limited storage capacity. Furthermore, changes in the recession constantly affect the delay in head reduction, influencing the MRC’s shape. This study underscores the significance of the relationship between recession coefficients, recession constants, and MRC shape in understanding groundwater flow dynamics. These findings provide valuable insights for more effective water resource management planning in small watershed areas.